Loss of hippocampal serine protease BSP1/neuropsin predisposes to global seizure activity. - Davies, B; Kearns, I; Ure, J; Davies, C; Lathe, R (2001)
Serine proteases in the adult CNS contribute both to activity-dependent structural changes accompanying learning and to the regulation of excitotoxic cell death. Brain serine protease 1 (BSP1)/neuropsin is a trypsin-like serine protease exclusively expressed, within the CNS, in the hippocampus and associated limbic structures. To explore the role of this enzyme, we have used gene targeting to disrupt this gene in mice. Mutant mice were viable and overtly normal; they displayed normal hippocampal long-term synaptic potentiation (LTP) and exhibited no deficits in spatial navigation (water maze). Nevertheless, electrophysiological studies revealed that the hippocampus of mice lacking this specifically expressed protease possessed an increased susceptibility for hyperexcitability (polyspiking) in response to repetitive afferent stimulation. Furthermore, seizure activity on kainic acid administration was markedly increased in mutant mice and was accompanied by heightened immediate early gene (c-fos) expression throughout the brain. In view of the regional selectivity of BSP1/neuropsin brain expression, the observed phenotype may selectively reflect limbic function, further implicating the hippocampus and amygdala in controlling cortical activation. Within the hippocampus, our data suggest that BSP1/neuropsin, unlike other serine proteases, has little effect on physiological synaptic remodeling and instead plays a role in limiting neuronal hyperexcitability induced by epileptogenic insult.